Prevalence of leptospirosis in animals in and around Thrissur - Manju Soman (Department of Microbiology, College of Veterinary and Animal Sciences, 2004)
A study was undertaken to assess the prevalence of leptospirosis in animals and man, in and around Thrissur. A total of 501 sera samples, collected from dogs, cattle, pigs, rodents (bandicoots and rats) and human beings were subjected to serologic testing, for detection of Leptospira specific antibodies, by MAT, PHA and indirect IgG ELISA. Isolation of Leptospira was tried from blood of clinically suspected cases of human and canine leptospirosis and from kidney tissues of rodents. The study revealed the presence of antibodies against Leptospira in human beings and all the four species of animals examined by the three tests employed. The prevalence rates detected by MAT in canines, bovines, porcines, murines and human beings were 36.36 per cent, 47 per cent, 23.8 per cent, 21.42 per cent and 54.54 per cent respectively. Out of 30 human blood samples subjected to isolation trials in Fletcher'slEMJH semisolid media with enrichment, Leptospira could be isolated from a single human patient, in Fletcher's semisolid medium with 10 per cent rabbit serum. Of the 35 rodent kidney tissues tried for isolation in Fletcher's semi solid media, leptospires were isolated from three bandicoots and two rats. Indirect ELISA was found to be most sensitive, of the three tests,for rapid screening of the population for leptospirosis, while PHA was found to be a fairly good test for diagnosis of acute leptospirosis. The MAT proved to be the most specific test which could also identify the serogroup identity of the infecting Leptospira. Leptospira pomona and L. australis were detected by MAT as the common serogroups prevalent in man, animals and rodents in this area. The prevalence of common leptospiral serovars in animals and man, indicated that human beings which were the end hosts for Leptospira could have acquired the infection mostly from animals like dogs, cattle and pigs, while the isolation ofleptospires from rodents revealed the carrier status of these animals.